2019
DOI: 10.1016/j.nbd.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia leads to exacerbation of ischemic brain damage: Role of GluN2A NMDA receptors

Abstract: Hyperhomocysteinemia has been implicated in several neurodegenerative disorders including ischemic stroke. However, the pathological consequences of ischemic insult in individuals predisposed to hyperhomocysteinemia and the associated etiology are unknown. In this study, we evaluated the outcome of transient ischemic stroke in a rodent model of hyperhomocysteinemia, developed by subcutaneous implantation of osmotic pumps containing L-homocysteine into male Wistar rats. Our findings show a 42.3% mortality rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 115 publications
(166 reference statements)
0
16
0
Order By: Relevance
“…Whereas NMDARs containing GluN2A/C or D subunits did not reveal desensitization during the HCY activation [12,13], currents through GluN1/GluN2B NMDARs briefly declined to about 15% of the peak amplitude because of the desensitization [12]. This observation exhibits why NMDARs containing GluN2A subunits, but not those of GluN2B, mostly contribute to HCY-induced excitotoxicity in cortical neurons [12][13][14][15][16]. Cerebellar neurons expressing NMDARs containing GluN2C or 2D are also sensitive to the excitotoxic action of HCY since these receptors do not reveal desensitization during the HCY activation [13].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Whereas NMDARs containing GluN2A/C or D subunits did not reveal desensitization during the HCY activation [12,13], currents through GluN1/GluN2B NMDARs briefly declined to about 15% of the peak amplitude because of the desensitization [12]. This observation exhibits why NMDARs containing GluN2A subunits, but not those of GluN2B, mostly contribute to HCY-induced excitotoxicity in cortical neurons [12][13][14][15][16]. Cerebellar neurons expressing NMDARs containing GluN2C or 2D are also sensitive to the excitotoxic action of HCY since these receptors do not reveal desensitization during the HCY activation [13].…”
Section: Introductionmentioning
confidence: 84%
“…The inhibition of PKA or PKC blocked ouabain-induced neuroprotection against HCY but not against Glu neurotoxicity. This observation can be related to the NMDAR subtype selectivity of HCY because GluN2A, but not GluN2B NMDAR subunits, mostly contribute to HCY toxicity in cortical neurons [12,[14][15][16] and reflect extensive recruitment of different glutamate ionotropic and metabotropic receptors and transporters in glutamate neurotoxicity.…”
Section: Apoptosis At Long-term Excitotoxic Stressmentioning
confidence: 98%
“…Whereas NMDARs containing GluN2A/C or D subunits did not reveal desensitization during the HCY activation [12,13], currents through GluN1/GluN2B NMDARs brie y declined to about 15 % of the peak amplitude because of the desensitization [12]. This observation exhibits why NMDARs containing GluN2A subunits, but not the GluN2B ones, mostly contribute to HCY-induced excitotoxicity in cortical neurons [12][13][14][15][16]. Cerebellar neurons expressing NMDARs containing GluN2C or 2D are also sensitive to the excitotoxic action of HCY since these receptors do not reveal desensitization during the HCY activation [13].…”
Section: Introductionmentioning
confidence: 84%
“…The inhibition of PKA or PKC blocked ouabain induced neuroprotection against HCY, but not against Glu neurotoxicity. This observation can be related to the NMDAR subtype selectivity of HCY because GluN2A, but not GluN2B NMDAR subunits, mostly contribute to HCY toxicity in cortical neurons [12,[14][15][16] [17][18][19], while HCY causes sustained p38 MAPK activity [14]. As a result, p38 MAPK inhibition can protect neurons from short-term, but not long-term activation of NMDARs [62].…”
Section: Apoptosis At Long-term Excitotoxic Stressmentioning
confidence: 99%
“…In the adult forebrain, GluN1/GluN2A containing NMDARs (GluN2A‐NMDAR) and GluN1/GluN2B containing NMDARs (GluN2B‐NMDAR) are the two most predominant functional NMDARs (Dingledine et al ). In earlier studies, we have shown that GluN2A‐NMDAR plays a key role in homocysteine‐induced neurotoxicity and exacerbation of ischemic brain damage (Poddar and Paul ; Poddar and Paul ; Jindal et al ). These findings show that the intracellular neurotoxic signaling cascade downstream of homocysteine‐GluN2A‐NMDAR stimulation involves Ca 2+ ‐dependent sustained activation of extracellular‐regulated kinase/mitogen‐activated protein kinase (ERK MAPK).…”
mentioning
confidence: 99%